General V.P. Malik, India’s Military Conflicts and Diplomacy: An Inside View of Decision Making - Ms. Huma Rehman (CISS Insight Journal, 2014)
Indian Military Conflict and Diplomacy by General V.P. Malik would be of interest to many Pakistanis as it discusses civil-military relations in India and several operations carried out by the Indian armed forces inside and outside the Indian territories. The author had been a part of them and gives Indian perspective on these operations. General V.P. Malik is a retired Indian army chief and had served in many important positions before taking over his responsibilities as head of the army. He, therefore, had the advantage of observing many events, in which Indian army played a role, from close quarters. The author describes Operation Pawan in Sri Lanka (1987), and Operation Cactus in Maldives (1988) in some detail. However of more interest to Pakistani readers would be the chapter on Kargil Conflict (1999). Operation Pawan and Kargil have been discussed at length as. The author blames lack of timely and actionable intelligence, on ground situation in Sri Lanka and activities of Tamil supporters in India’s Tamil Nadu state for failure of operation Pawan. The author is all praise for successful operation by the Indian military in the Maldives which thwarted an attempted coup de’ate for taking over power by Abdullah Lutfee, a businessman with the support of People’s Organization of Tamil Elam (POLTE).